Combined Bile Duct and Pancreatic Duct Injuries during Distal Gastrectomy for Obstructing Peptic Ulcer Disease - Narendra Pandit; Kunal Bikram Deo (Case Reports in Surgery)
A combination of bile and pancreatic duct injuries is very rare. Anomalous ductal anatomy, distorting duodenal fibrosis, and pancreatic atrophy predispose to this untoward complication during performance of distal gastrectomy for benign peptic stricture. The technical challenges posed by this complication and experience gained by managing it are shared.